Design and Development of a Metamaterial Enhanced Microstrip Antenna Integrated With a Monopulse Comparator for Tracking Applications - V M Jayakrishnan; R. V. Sanjika Devi; Dhanesh G. Kurup (IEEE Access)
This paper presents the design and development of a metamaterial-enhanced pentagonal patch antenna integrated with a monopulse comparator operating at 2.4 GHz for S-band radar tracking and UAV applications. The metamaterial structure is specifically designed to reduce cross-polarization and enhance the gain of the conventional pentagonal patch antenna, thereby resulting in enhanced antenna performance. The primary contribution and novelty of this research work are the successful system-level integration of the metamaterial-based antennas with a monopulse comparator and the experimental validation of their tracking capabilities. The proposed system offers a cost-effective and affordable solution for S-band radar tracking applications. Each metamaterial enhanced antenna was individually characterized and validated prior to their final integration into the monopulse comparator. The measured gain of the monopulse tracking system is 19 dBi, and the integrated system achieves excellent sum and difference responses with a null depth of approximately −55 dB, indicating high tracking precision. Real-time tracking experiments were also conducted using transmitter antennas such as a log-periodic dipole array (LPDA) and a sleeve dipole, placed at a far-field distance from the integrated system in an indoor environment. The results demonstrate that, there is a strong agreement between simulated and measured responses and the designed system is capable of accurately tracking the target with reduced errors making it highly suitable for modern UAV and radar applications.